MEMOIR AND THE EROTIC: A READING OF ATMAKATHAIKKU ORU AAMUGHAM (PREFACE TO AN AUTOBIOGRAPHY)AND ANTHARJANAM: MEMOIRS OF A NAMBOODIRI WOMAN - SREEDEVI SANTHOSH (Samyukta: A Journal of Women’s Studies, 2010)
The articulation of sexuality within the malayala brahmana community is interspersed with the narrative representation of it in memoirs. Memories of everyday inconspicuousness of the Antherjanam considered “asuryampashyakal”, their semantics of appearance, elaborate ritualistic seclusion (ghosha) within the confines of the “illam”define gender identities within the community. The paper considers these imaging techniques as cryptography of his /her moral values imposed by the community of “theocratic feudalists”. The paper interprets clothing and nudity as a visual text type reinforcing values of specific social identities and becomes an operator of social control. In the caste – Sub Caste society of Kerala, sexuality was patrolled and channelized for the “reproduction of caste bodies”, to perpetuate the uncontaminated continuity of caste, purity of the body and of rituals that define their everyday. Through its “unstatedness” and dismissal, female sexuality gets inscribed forcefully into narratives within the region. The study chooses to consider two popularly known memoirs within the community, Lalithambika Memoir and the Erotic: A Reading of Atmakathaikku Oru Aamugham (Preface to an Autobiography) and Antharjanam: Memoirs of A Namboodiri Woman Antharjanam’s Atmakathaikku Oru Aamugham (Preface to an Autobiography) and Antharjanam: Memoirs of A Namboodiri Woman, to understand coercive control mechanisms that define femininity and evolving gender identities within the community.